2013
DOI: 10.1163/15691330-12341272
|View full text |Cite
|
Sign up to set email alerts
|

Who Joins Trade Unions? Testing New Sociological Explanations

Abstract: Why do some workers join trade unions and others do not? This article attempts to shed new light on this question by considering how certain behavioural and attitudinal differences among workers shape their propensities to join trade unions.In particular, it is hypothesized that variations in civic and political engagement, as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Schnabel and Wagner (2007) report no significant effects of either social background or ideology in their cross-sectional, cross-country study examining the individual propensity to be organized in a union, whereas Ebbinghaus et al (2011) do find support for moderate effects of ideology on union membership, using the same cross-sectional data source as Schnabel and Wagner (2007). In a cross-country, cross-sectional study of the effects of cultural values and civic and political engagement, Kollmeyer (2013) observes support for positive effects of left-leaning ideological views on union membership but not for post-materialist values. This inconsistency in the results suggests that different types of methods, the choice of variables and measurements used and included in the models may indeed affect the results, as noted by for example Riley (1997).…”
Section: Class Ideology Collective Identity and Collective Mobilizamentioning
confidence: 98%
“…Schnabel and Wagner (2007) report no significant effects of either social background or ideology in their cross-sectional, cross-country study examining the individual propensity to be organized in a union, whereas Ebbinghaus et al (2011) do find support for moderate effects of ideology on union membership, using the same cross-sectional data source as Schnabel and Wagner (2007). In a cross-country, cross-sectional study of the effects of cultural values and civic and political engagement, Kollmeyer (2013) observes support for positive effects of left-leaning ideological views on union membership but not for post-materialist values. This inconsistency in the results suggests that different types of methods, the choice of variables and measurements used and included in the models may indeed affect the results, as noted by for example Riley (1997).…”
Section: Class Ideology Collective Identity and Collective Mobilizamentioning
confidence: 98%
“…As has been well established in the current literature, individuals partake in the sharing economy for a variety of reasons, ranging from monetary to social and hedonic benefits (Bucher et al ., ). These divergent interests can be further exacerbated by political differences (Korpi and Shalev, ), where previous studies have found that left‐wing orientations correlate positively with union membership (Kollmeyer, ; Jansen, ) and attitudes towards collective action (Hague et al ., ; Turner and D'Art, ).…”
Section: Prior Researchmentioning
confidence: 99%
“…Historically, political cleavages between the left and the right are closely tied to interest representation in the system of industrial relations (Almond, 1958; Korpi and Shalev, 1979; Lipset, 1961): with, on the one hand, trade unions linking to labor parties to promote welfare distribution and social security, and on the other hand, business organizations linking with right-wing parties to advocate capitalist markets and limitation of government interventions. As an expression of such traditional left/right divisions, previous studies on employees have systematically found that left-wing political orientations positively correlate with trade union membership (Kollmeyer, 2013; Schnabel and Wagner, 2005). Recent research has shown that solo self-employment in the Netherlands is associated with heterogeneous political preferences, and that growing segments of self-employed voters move away from typical right-wing voting behavior, and instead support ‘new-left’ and ‘social-liberal’ parties (Jansen, 2016, 2017).…”
Section: Theory and Hypothesesmentioning
confidence: 99%